Evolutionary Path of Development of Artificial Intelligence (AI) and Patterns of Knowledge Convergence over the Second and Third AI Booms - Kumiko Miyazaki; Santiago Ruiz Navaz; Ryusuke Sato (STI Policy and Management Journal, 2019)
Although AI was coined by John McCarthy 60 years ago, AI has been confined to the academic and scientific research domain. AI has been through several booms and we have currently reached the 3rd AI boom which followed the 2nd AI boom centering mainly on expert systems. The current AI boom started around 2013 and AI is beginning to affect corporate management and operations. AI has been evolving over six decades but it seems that the current boom is different from the previous booms. In this paper, we attempt to elucidate the evolutionary path of development of AI and the structural patterns of knowledge convergence in the current and previous booms.For this purpose we have set 2 main objectives1) To characterize the first (1B), second (2B) and the current, third (3B) AI boom2) To analyze the structure of knowledge convergence around AIRQ   How have the key technologies and the applications of AI changed over time, in the 2B and the 3B? An innovative method has been used to identify the characteristics of AI and the evolutionary path of knowledge convergence over the booms.